2021
DOI: 10.1038/s41598-021-85394-0
|View full text |Cite|
|
Sign up to set email alerts
|

Differential normal skin transcriptomic response in total body irradiated mice exposed to scattered versus scanned proton beams

Abstract: Proton therapy allows to avoid excess radiation dose on normal tissues. However, there are some limitations. Indeed, passive delivery of proton beams results in an increase in the lateral dose upstream of the tumor and active scanning leads to strong differences in dose delivery. This study aims to assess possible differences in the transcriptomic response of skin in C57BL/6 mice after TBI irradiation by active or passive proton beams at the dose of 6 Gy compared to unirradiated mice. In that purpose, total RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For database construction, we performed text mining in PubMed, using appropriate keywords across studies that experimentally address the overall effect of five high- and low-LET radiation types of interest in a broad range of mammalian cell types, including human, mouse and rat study model systems. The database includes 7436 entries, with a total of 3730 unique genes derived from 14 tissues/cell lines [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For each entry, the following information was provided: Differential expression of genes: The expression status of the corresponding genes (i.e., up or downregulated in irradiated compared to non-irradiated tissue/cell control groups).…”
Section: Resultsmentioning
confidence: 99%
“…For database construction, we performed text mining in PubMed, using appropriate keywords across studies that experimentally address the overall effect of five high- and low-LET radiation types of interest in a broad range of mammalian cell types, including human, mouse and rat study model systems. The database includes 7436 entries, with a total of 3730 unique genes derived from 14 tissues/cell lines [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For each entry, the following information was provided: Differential expression of genes: The expression status of the corresponding genes (i.e., up or downregulated in irradiated compared to non-irradiated tissue/cell control groups).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were included if they were peer-reviewed, original research articles published in the English language, if a validated patient-reported outcomes tool was used to measure quality of life, and if participants were children diagnosed with cancer between ages 0 to 21 years [ 17 ]. Studies were eligible if participants received external beam RT (XRT or PRT), with total body irradiation excluded, as a comparable technique using particle therapy is not in clinical use [ 18 ]. If an analysis of a patient cohort included patients with and without RT treatment, 50% or more participants were required to have received RT.…”
Section: Methodsmentioning
confidence: 99%
“…During the U19 award period, seven trainees benefited from resources provided by the program and were able to parlay their experiences into presentations at meetings of the RRS, the International Congress of Radiation Research, and the American Society for Therapeutic Radiation Oncology. Most of those fellows that were supported by the MCW Core continue to publish papers in the radiation field ( Prevost et al 2018 ; Lenarczyk et al 2019 ; Wunderle et al 2019 ; Lenarczyk et al 2020 ; Leduc et al 2021 ; Raber et al 2021 ; Hsu et al 2022 ; Liu et al 2022 ) and obtain follow-on funding (e.g. pilots or full research grants).…”
Section: Mentoring the Next Generations: Training And Education Effortsmentioning
confidence: 99%